Sulawesi Development Diagnostic : Achieving Shared Prosperity - World Bank (World Bank, Washington, DC, 2016)
The sulawesi development diagnostic aims to examine the island’s growth drivers and constraints, analyze why growth is not inclusive and what segment of the population is lagging. This report looks into the pace and pattern of growth and examines benefits different segments of the population derived from sulawesi’s economic growth, for example, poor versus non‐poor. The report also analyzes why growth has not been unconvincingly inclusive, particularly in terms of equality of opportunity, poverty reduction and employment creation. The analysis also identifies constraints to sustained and inclusive development such as education and health outcomes. The analysis will focus on the agriculture, extractive industries and infrastructure in its examination of drivers and constraints of growth. This report matches the development challenges identified with a discussion of the current policies and propose potential solutions for sulawesi. The research in this report is based on with local stakeholders interviews and analysing an extensive set of databases and secondary materials. The report is organized into ten chapters broken into two parts. Following the introductory chapter, Part one of this report comprises of three chapters that analyze the challenges for achieving inclusive growth in Sulawesi. Chapter 2 provides an overview of Sulawesi’ growth pattern and growth drivers; Chapter 3 presents analysis showing that despite reduction in poverty inequality has increased; Chapter 4 identifies why growth has not been more inclusive and what challenges Sulawesi faces. Part two of the report comprising of Chapter 5 to 9 discusses each challenge in more detail and proposes policy measures for each challenge. Chapter 5 analyzes the first challenge of how to make agricultural sector more productive in order to increase income for labor participants in the sector. This chapter analyzes the agriculture sector through the lens of Sulawesi’s three main commodities: rice, cocoa, and maize. Chapter 6 analyzes the challenge of developing the rural nonfarm sector so that it can generate alternative and higher income employment for the rural poor. Chapter 7 discusses why Sulawesi’s extractive industry is not inclusive and offers ideas for improvement so that more communities benefit from its growth. Chapter 8 analyzes why health and education outcomes are low in Sulawesi and identifies the main constraints for effective service delivery, particularly for the vulnerable and marginalised population. Chapter 9 assesses Sulawesi’s infrastructure challenges and how increased access to public infrastructure is crucial for ensuring Sulawesi achieves sustained economic growth. Chapter 10 will conclude with a conclusion of the key priorities for Sulawesi and a discussion on the future prospects of the region.